Increased numbers of DNA-damaged spermatozoa in samples presenting an elevated rate of numerical chromosome abnormalities. - Enciso, M; Alfarawati, S; Wells, D (2013)
STUDY QUESTION: Is there a relationship between DNA damage and numerical chromosome abnormalities in the sperm of infertile patients? SUMMARY ANSWER: A strong link between DNA fragmentation and the presence of numerical chromosome abnormalities was detected in human sperm. Chromosomally abnormal spermatozoa were more likely to be affected by DNA fragmentation than those that were chromosomally normal. WHAT IS KNOWN ALREADY: Several studies have described the presence of elevated levels of DNA damage or chromosome defects in the sperm of infertile or subfertile men. However, the nature of the relationship between sperm DNA damage and chromosome abnormalities is poorly understood. The fact that some assisted reproductive techniques have the potential to allow abnormal spermatozoa to achieve oocyte fertilization has led to concerns that pregnancies achieved using such methods may be at elevated risk of genetic anomalies. STUDY DESIGN, SIZE, DURATION: For this prospective study, semen samples were collected from 45 infertile men. PARTICIPANTS, SETTING, METHODS: Samples were assessed for DNA fragmentation using the Sperm Chromatin Dispersion Test (SCDt) and for chromosome abnormalities using multi-colour fluorescence in situ hybridization (FISH) with probes specific to chromosomes 13, 16, 18, 21, 22, X and Y. Additionally, both parameters were assessed simultaneously in 10 of the samples using a protocol combining SCDt and FISH. MAIN RESULTS AND THE ROLE OF CHANCE: A significant correlation between the proportion of sperm with a numerical chromosome abnormality and the level of DNA fragmentation was observed (P < 0.05). Data from individual spermatozoa subjected to combined chromosome and DNA fragmentation analysis indicated that chromosomally abnormal sperm cells were more likely to display DNA damage than those that were normal for the chromosomes tested (P < 0.05). Not only was this association detected in samples with elevated levels of numerical chromosome abnormalities, but it was also evident in samples with chromosome abnormality rates in the normal range. LIMITATIONS, REASONS FOR CAUTION: The inability to assess the entire chromosome complement is the main limitation of all studies aimed at assessing numerical chromosome abnormalities in sperm samples. As a result, some of the sperm classified as 'chromosomally normal' may be aneuploid for chromosomes that were not tested. WIDER IMPLICATIONS OF THE FINDINGS: During spermatogenesis, apoptosis (a process that involves active DNA degradation) acts to eliminate abnormal sperm. Failure to complete apoptosis may explain the coincident detection of aneuploidy and DNA fragmentation in some spermatozoa. In addition to shedding light on the biological mechanisms involved in the processing of defective sperm, this finding may also be of clinical relevance for the identification of patients at increased risk of miscarriage or chromosomally abnormal pregnancy. In some instances, detection of elevated sperm DNA fragmentation may indicate the presence of chromosomal abnormalities. It may be worth considering preimplantation genetic screening (PGS) of embryos produced using such samples in order to minimize the risk of aneuploidy.